Impact of PV Generation on Voltage Profile and MW Losses inSouth-West LibyanDistribution Network - S.A.Tajeldinr, I.S.Naser, Mohamad Hossin, M.N.Hussin (Journal of Pure & Applied Sciences, 2020)
Recently, the photovoltaic (PV) has been dramatic development throughout the World especially, connected to the distribution networks. The connection of PV energy resources challenges the planning and operation of the grid. This paper aims to study and provide understanding on the impact of PV generation on voltage profile and MW losses in the south-west Libyan distribution network. For this purpose a 27-bus Takarkibah distribution network has been modelled in Power World Simulator. Finally, the results did show an improvement in the voltage profile and MW losses of the network for both the higher penetration level and multiple locations of the PV.